Particle and prefix nouns An analytical case study of their morphology and semantics - (:unkn) unknown (ERICH SCHMIDT VERLAG, 2008)
Particles and prefixes preceding the simple verb have a decisive effect on its semantic content, and particle and prefixed nouns derived from such verbs reflect this state of affairs. These deverbal nouns are analysed on the basis of four simple verbs, fallen, gehen, legen and setzen, and three particles/prefixes, auf-, durch- and ver-, using deverbal nouns with the suffixes -ung, -er, -e and the zero-morpheme because of their frequency and high productivity. The corpus for this study is provided by the six-volume Brockhaus/Wahrig Deutsches Worterbuch. The 82 nouns found there are analysed semantically and assigned to the two abstract semantic categories, nomina actionis and nomina acti, and the five concrete categories, nomina patientis/facti, nomina instrumenti, nomina subjecti or agentis, locative and collective nouns. The results are summarised in tables. The tables show among other things that all simple verbs are not equally suitable for nominalisation, that the nominalisation potential is affected by the verb prefix, that the main semantic function of the suffix -ung is the formation of nomina actionis, that formations with the zero-morpheme and the prefix -e account for about 60% of the abstract nouns, and finally that the main function of the suffix -er is the formation of nomina subjecti/agentis.